Audiovisual temporal integration: Cognitive processing, neural mechanisms, developmental trajectory and potential interventions. (16th March 2020) - Zhou, Han-yu; Cheung, Eric F.C.; Chan, Raymond C.K.
Abstract: To integrate auditory and visual signals into a unified percept, the paired stimuli must co-occur within a limited time window known as the Temporal Binding Window (TBW). The width of the TBW, a proxy of audiovisual temporal integration ability, has been found to be correlated with higher-order cognitive and social functions. A comprehensive review of studies investigating audiovisual TBW reveals several findings: (1) a wide range of top-down processes and bottom-up features can modulate the width of the TBW, facilitating adaptation to the changing and multisensory external environment; (2) a large-scale brain network works in coordination to ensure successful detection of audiovisual (a)synchrony; (3) developmentally, audiovisual TBW follows a U-shaped pattern across the lifespan, with a protracted developmental course into late adolescence and rebounding in size again in late life; (4) an enlarged TBW is characteristic of a number of neurodevelopmental disorders; and (5) the TBW is highly flexible via perceptual and musical training. Interventions targeting the TBW may be able to improve multisensory function and ameliorate social communicative symptoms in clinical populations. Highlights: Asynchronous and synchronous audiovisual perception are correlated with different brain networks. The width of the TBW is modulated by both top-down and bottom-up factors. The width of the TBW follows a U-shaped developmental trajectory across the lifespan. Atypical TBW is a shared characteristic of different neurodevelopmental disorders. Perceptual and musical training may be able to narrow the audiovisual TBW.